Assessing the Role of the International System on the Global Economy - Kenwilliams Nyakomitah (Journal of World Economy, 2023)
This research endeavors to explore the intricate relationship between the international system and the global economy. It seeks to dissect how the international system, comprising international organizations, treaties, trade agreements, and political alliances, influences the dynamics, growth, and stability of the global economy. This study is motivated by the need to comprehend the evolving global economic landscape in the context of the international system and to provide insights that can guide policymakers and economists in promoting a more equitable and sustainable global economic order. An engagement with international relations seeks to underscore the historical development of the concept of the sovereign state, the international system, and the global economy. In addition, there are discussions on the cultural, political, and moral arguments that are used in international relations. In essence, a study in international relations is the bedrock upon which successful studies into world politics are based on.